2022
DOI: 10.4269/ajtmh.21-1143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Combined Whole-cell Antigen and Recombinant Hemolysis Co-regulated Protein 1-Enzyme-linked Immunosorbent Assays Reveals Underdiagnosed Cases of Melioidosis in Vietnam

Abstract: Melioidosis is a fatal infectious disease in the tropics and subtropics. Currently, bacterial culture is the gold standard for diagnosis of the disease, but its sensitivity is relatively low. In this study, we evaluated four ELISAs using sera collected from culture-confirmed cases of melioidosis (n = 63), cases with other bacterial infections (n = 62), and healthy donors (n = 60). Antigens used for ELISAs were the whole-cell (WC) antigens and recombinant proteins of hemolysis co-regulated protein 1 (Hcp1), Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Multiple studies have demonstrated that Hcp1 is highly immunogenic, reacting particularly strongly to human melioidosis sera [ 136 , 139 ] and glanders sera from mice, horses, and one human [ 132 , 140 ]. PBMCs from melioidosis seropositive donors also respond to stimulation with Hcp1, correlating with patient survival [ 141 ].…”
Section: Type 6 Secretion Systemsmentioning
confidence: 99%
“…Multiple studies have demonstrated that Hcp1 is highly immunogenic, reacting particularly strongly to human melioidosis sera [ 136 , 139 ] and glanders sera from mice, horses, and one human [ 132 , 140 ]. PBMCs from melioidosis seropositive donors also respond to stimulation with Hcp1, correlating with patient survival [ 141 ].…”
Section: Type 6 Secretion Systemsmentioning
confidence: 99%